2015
DOI: 10.1155/2015/495684
|View full text |Cite
|
Sign up to set email alerts
|

The History, Mechanism, and Clinical Application of Auricular Therapy in Traditional Chinese Medicine

Abstract: Auricular therapy includes acupuncture, electroacupuncture, acupressure, lasering, cauterization, moxibustion, and bloodletting in the auricle. For 2500 years, people have employed auricular therapy for treating diseases, but the methods have been limited to bloodletting and cauterization. Only after 1957, the international scientific community became aware that the map of the ear resembles an inverted fetus, its introduction has led to auricular acupuncture (AA) becoming a more systemic approach, and, followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 118 publications
3
149
0
26
Order By: Relevance
“…Many reports have showed that it was the good way to regulate the dysfunction of some organs such as heart, lung and stomach, etc. through stimulating the area of cavum conchae densely distributed ABVN, but not other areas on auricle, because NTS could mediate many reflexes including respiratory and GI reflexes to regulate organ functions[25,44]. This is the reason why there was no significant change of the expression of nNOS mRNA in antrum in sham AEA group by stimulating earlobe in this study.…”
Section: Dicussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Many reports have showed that it was the good way to regulate the dysfunction of some organs such as heart, lung and stomach, etc. through stimulating the area of cavum conchae densely distributed ABVN, but not other areas on auricle, because NTS could mediate many reflexes including respiratory and GI reflexes to regulate organ functions[25,44]. This is the reason why there was no significant change of the expression of nNOS mRNA in antrum in sham AEA group by stimulating earlobe in this study.…”
Section: Dicussionmentioning
confidence: 77%
“…Auricular acupuncture (AA), one of the most important branches of acupuncture, is also used in Europe and China with long history [2526]. which looked as a diagnostic method and effective treatment of visceral diseases including functional dyspepsia (FD)[27–28]in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The research on history, mechanism, and clinical application of auricular therapy has experienced a long process [24]. The nomenclature, location method, and consistency between name and location are three topics in the research field of international standardization of AAPs.…”
Section: Resultsmentioning
confidence: 99%
“…These devices can be left temporarily in place using adhesive tape [10]. Somatic reflexology posits that diseases are projected onto the ear at regular and measureable zones [11,12]. While no anatomical pathways exist to directly connect inner organs with the ear, limited functional magnetic resonance imaging has corroborated these projections [12].…”
Section: Auricular Acupuncturementioning
confidence: 99%
“…Somatic reflexology posits that diseases are projected onto the ear at regular and measureable zones [11,12]. While no anatomical pathways exist to directly connect inner organs with the ear, limited functional magnetic resonance imaging has corroborated these projections [12]. Battlefield acupuncture is an auricular acupuncture technique that can be learnt in a 4-hour workshop [2].…”
Section: Auricular Acupuncturementioning
confidence: 99%